Tingkat Kesejahteraan Buruh Tani Tanaman Pangan di Kecamatan Aluh-Aluh Kabupaten Banjar - Danhartani Danhartani; Eka Radiah; Usamah Hanafie (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The study is purposed to know landless farmers welfare and to identify their problems. Landless farmer refers to farmer who cultivate crop in agricultural land owned by others. From 278 landless farmers, 30 per cent (83 farmers) were randomly selected as respondents. About 66.27 per cent of respondent work with 1 – 2.5 hectares, while the rest work with 3 – 3.5 hectares. The study finds, landless farmer in Kecamatan Aluh-Aluh are below the poverty line as their income only Rp 19,102 below World Bank standard US$ 2 per day (Rp. 19,800). The study also finds that farmer who works on 1 – 2.5 hectares has income below Rp 9,800, while farmers who work with 3 – 3.5 hectares generate income more than Rp 9,800. Problem faced by farmers are: low yield price in harvest season, unavailable of credit, and sea-water intrusion which lead to harvest failure.